2017
DOI: 10.1590/1980-57642016dn11-030012
|View full text |Cite
|
Sign up to set email alerts
|

High education accelerates cognitive decline in dementia: A brief report from the population-based NEDICES cohort

Abstract: High education has been associated with faster cognitive decline after diagnosis of Alzheimer's disease (AD), but it is unclear whether these findings extend to other dementia subtypes.OBJECTIVE:We investigated whether educational attainment influences the cognitive trajectories of older adults with different dementia subtypes.METHODS:All participants were selected from NEDICES, a prospective population-based cohort study of Spanish older adults. A total sample of 53 individuals with dementia completed the MMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
2
7
1
Order By: Relevance
“…One particularly interesting finding of this study is that higher education (more years of education) predicts cognitive worsening in PD (Table 3). Indeed, the role of education as a risk factor for cognitive impairment is still debated: lower education was observed to be a risk factor of cognitive impairment (Reuser et al, 2011;Contador et al, 2017), but, at the same time, high education has been found to lead to more rapid cognitive decline (Meng and D'Arcy, 2012;Contador et al, 2017). However, in our study, this effect was not stable in multivariate regression analysis, and, perhaps, needs further focused investigation.…”
Section: Discussioncontrasting
confidence: 65%
“…One particularly interesting finding of this study is that higher education (more years of education) predicts cognitive worsening in PD (Table 3). Indeed, the role of education as a risk factor for cognitive impairment is still debated: lower education was observed to be a risk factor of cognitive impairment (Reuser et al, 2011;Contador et al, 2017), but, at the same time, high education has been found to lead to more rapid cognitive decline (Meng and D'Arcy, 2012;Contador et al, 2017). However, in our study, this effect was not stable in multivariate regression analysis, and, perhaps, needs further focused investigation.…”
Section: Discussioncontrasting
confidence: 65%
“…The cognitive reserve theory posits that highly educated individuals cope better with AD pathology [ 8 , 44 ] and do not show dementia symptoms until they have substantial amount of pathological burden in the brain. However, when more educated individuals started to show dementia symptoms, they showed steeper cognitive decline [ 45 ]. Likewise, young individuals have greater neural reserve and need greater pathological burden to show dementia symptoms than old individuals [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic search for studies investigating whether education is related to the progression of cognitive changes after dementia diagnosis revealed eight nonoverlapping studies (total N = 1,815), four of which (total N = 555) indeed reported faster declines for more highly educated individuals on measures of cognitive function during the years immediately after a dementia diagnosis). Of those studies, two reported data from very small samples (Contador, Bermejo-Pareja, Pablos, Villarejo, & Benito-Leon, 2017;Unverzagt, Hui, Farlow, Hall, & Hendrie, 1998). However, Andel, Vigen, Mack, Clark, and Gatz (2006) studied a larger sample of 171 individuals with a diagnosis of Alzheimer's disease in a longitudinal cohort study.…”
Section: Education and Cognitive Decline Before And After Dementia DImentioning
confidence: 99%